GHEF 2016: PLANNING FOR FUTURE HIGHER EDUCATION SCENARIOS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
GEORGE TOWN, PENANG, 7 April 2016 – “There would be tremendous changes affecting various aspects of higher education institutions in the future; changes affecting the functions, structures and institutional foundations.”